Dimensioning and evaluation of the radio frequency orbital resource - Balabanov, Boncho; Petrov, Georgi; Stancheva, Anushka (Yearbook Telecommunications, 2016)
This paper shows a new concept for optimization of Radio frequency spectrum (RFS) orbital resource in international domain. The RFS resource is necessary for proper operation of different telecommunications systems. This resource has three physical dimensions: frequency bandwidth, space coverage area and time. RFS has also quality characteristics: quality (purity) of the spectrum, RFS load, RFS use (consumption), public and professional interest in the use of RFS. A novel model for dimensioning of RFS is described and a short explanation is shown.